Accuracy of bracket placement by orthodontists and inexperienced dental students - Armstrong David; Shen Gang; Petocz Peter; Darendeliler M. Ali (Sciendo, 2023)
Well-finished orthodontic treatment begins with accurate positioning of the brackets on the teeth.